2008
DOI: 10.1007/s00259-008-0838-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of functional recovery after revascularization using quantitative gated myocardial perfusion SPECT: a multi-center cohort study in Japan

Abstract: Backgrounds Prediction of left ventricular functional recovery is important after myocardial infarction. The impact of quantitative perfusion and motion analyses with gated single-photon emission computed tomography (SPECT) on predictive ability has not been clearly defined in multi-center studies. Methods A total of 252 patients with recent myocardial infarction (n=74) and old myocardial infarction (n=175) were registered from 25 institutions. All patients underwent resting gated SPECT using 99m Tc-MIBI, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The ML-based model developed in this study surpassed previous studies that utilized traditional myocardial perfusion imaging methods such as single-photon emission computed tomography (SPECT), speckle tracking echocardiography, and MCE, which reported AUCs ranging from 0.7 to 0.8 for myocardial function recovery prediction. 8 , 11 , 34 , 35 This demonstrates the substantial potential of the MCE radiomics-based ML model in identifying visually subtle yet highly predictive image features. Although a few reports exist on radiomics-based ML approaches in myocardial function prediction, 19 including the findings of Arian et al 36 which showed that MRI radiomics features combined with ML algorithms provided prognostic information regarding myocardial function in patients after coronary artery bypass grafting with an AUC similar to our report at 0.78, this study represents the first application of a radiomics-based ML approach in MCE.…”
Section: Discussionmentioning
confidence: 82%
“…The ML-based model developed in this study surpassed previous studies that utilized traditional myocardial perfusion imaging methods such as single-photon emission computed tomography (SPECT), speckle tracking echocardiography, and MCE, which reported AUCs ranging from 0.7 to 0.8 for myocardial function recovery prediction. 8 , 11 , 34 , 35 This demonstrates the substantial potential of the MCE radiomics-based ML model in identifying visually subtle yet highly predictive image features. Although a few reports exist on radiomics-based ML approaches in myocardial function prediction, 19 including the findings of Arian et al 36 which showed that MRI radiomics features combined with ML algorithms provided prognostic information regarding myocardial function in patients after coronary artery bypass grafting with an AUC similar to our report at 0.78, this study represents the first application of a radiomics-based ML approach in MCE.…”
Section: Discussionmentioning
confidence: 82%
“…In patients with CAD, LVEF was correlated with CA (r = 0.91), CW (r = 0.88), and SCI (r = 0.78). LVEF has previously been identified as one of the predictors of myocardial viability [17][18][19][20]. However, the information provided by LVEF alone might not be sufficient for it to serve as a predictive index [21,22].…”
Section: Discussionmentioning
confidence: 99%